Birds in the school yard: The impact of a science inquiry unit on local bird ecology on the environmental attitude and knowledge of Grade 4 Trinidadian students [PowerPoint presentation] - Kalloo, Rowena (My University, 2013)
In Trinidad and Tobago, teaching environmental science as situated knowledge at the primary level can be challenging because of a scarcity of resources and knowledge of local natural environments. This study raised questions on the extent to which a module on bird ecology could influence environmental attitudes of Trinidadian, primary schools students. Research suggests that children's attitudes to the environment are shaped by multi-sensory, inquiry-driven learning experiences in nature. It was predicted that there would be a high probability of an increase in students' pro-environmental attitudes and knowledge of local birds after exposure to the module. Twenty six, Standard 4 students in a low-income, urban environment were introduced to an eight-week multisensory, interactive module on local bird identification and ecology, which included an out-of-school field trip to a nature centre. Students' environmental attitudes were measured using questionnaires before and after treatment. Data were supplemented with qualitative observations, interviews, and a participatory mapping exercise. Statistical analysis indicated a significant difference in environmental attitudes (p=0.05), indicating that changes to attitudes were statistically significant and may be related to the quality of the intervention. The potential and challenges for introduction of this module into the local primary system of Trinidad and Tobago is discussed
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Environmental education; Primary school students; Primary school science; Science education; Birds; Student attitudes; Knowledge level; School yard ecology; Place based education; Conference papers; Trinidad and Tobago